Spatial impact analysis of trans-Yangtze highway fixed links: A case study of the Yangtze River Delta, China. (October 2020) - Liu, Weichen; Cao, Youhui; Wu, Wei; Guo, Jiaying
Abstract: As an important infrastructure connecting straits or rivers, the construction of fixed links has become an effective measure for improving traffic conditions and promoting socio-economic development in many countries and regions around the world. Thus, it has become a significant topic in the field of transport geography. Taking the Yangtze River Delta as its case area, this study proposes a spatial impact model of trans-Yangtze highway fixed links, consisting of three components: an accessibility model, modified gravity model, and traffic utilisation model, which are used to analyse, respectively, cross-Yangtze accessibility and changes to transport structure, cross-Yangtze urban interaction and changes to economic structure, and the utilisation relationship of fixed links. Making use of existing fixed links while planning and building new ones has become the basis for achieving regional integration and sub-regional cooperation in this area, the aim of which is to create the barrier-free circulation of elements. The results prove that this spatial impact model coincides with reality. The increase in the number of fixed links has significantly shortened cross-river travel time and facilitated a unification of north-south highway networks. It has also promoted the formation of a high-connection urban network along the river. Northern urban nodes have joined the southern economic circle and finally achieved north-south integration. There are complex relationships between fixed links and their hinterlands, showing obvious utilisation gaps between the links. The complete system of trans-Yangtze fixed links is comprised of several river crossing facilities and connected highways. The function of each link is related to its role in the regional highway network. From a small number of fixed links to the realisation of multiple trans-Yangtze bridges and tunnels with easy access to multiple arterial highways, a 'many-to-many' spatial pattern is created that ultimately leads to the evolution of regional transport and economic structures.